PURIFICATION OF SPERMATOGONIAL STEM CELLS FROM RAM TESTICULAR ISOLATE USING FICOLL DENSITY GRADIENT SEPARATION - BINSILA, B K; SELVARAJU, S; GHOSH, S K; PRASAD, J K; RAMYA, L; RAVINDRA, J P; BHATTA, R (The Indian Journal of Animal Reproduction, 2022)
Spermatogonial stem cells (SSCs) can be used to propagate male superior germ plasm and to preserve themale of high genetic merit and endangered species. The objective was to assess the efficiency of different Ficolldensity gradient separation in order to purify SSCs from the testicular cell isolates. The mixed testicular isolatesobtained after enzymatic digestion of testicular tissues was subjected to two different Ficoll density gradientmethods (method 1: Ficoll at 10 and 12% and method 2: Ficoll at 10, 12 and 16%). The percentage of SSCs(positive for PLZF, an SSC marker) obtained from the fractions, F12 media and F12-16 Interphase (FI) yielded(p
Keywords: Ficoll density gradient; PLZF positive; Ram; Spermatogonial stem cell; Testis